Relationship of mean grain size and sorting condition on Copepoda at seagrass bed of Sungai Pulai, Johor during coastal reclamation activity - Kassim, Zaleha; N. A, Syahidah; I.N.H., Ahmad (iConferences, 2021)
Benthic copepods use seagrass bed as their refuge and feeding area. The grain size and sorting condition in the area could be disturbed during coastal reclamation activities. A study was carried out to investigate the relationship between the density of families of harpacticoid copepods with the mean grain size and sorting condition of bottom sediment in the seagrass bed in Sungai Pulai Johor, during a coastal reclamation project. Samples of sediment within the seagrass plants and outside the vegetated area were collected in two sampling sessions in 2017 (September and December). In general, harpacticoid copepod density was higher in the vegetation (81.55±29.83 individual/10cm2) than the non-vegetation area (16.27±10.51 individual/10cm2). Pearson’s correlation analysis showed different result between the sampling periods. In September, harpacticoids were highly correlated with the grain size (r=0.939). Porcellidiidae, Miraciidae and Longipediidae were positively correlated with the grain size (r=1, r=0.997, r=0.996 respectively) but were negatively correlated with the sorting condition (r=-0.997, r=-0.992, r=-0.999 respectively). Harpacticoids had a very weak relationship with grain size (r=-0.295) and sorting condition (r=0.341) in December. The relationship between sediment condition and the harpacticoids might be dependent on the period of the sampling session. Longer period of sampling could give different result.